Mutu Es Krim Jagung Manis Dengan Penambahan Tepung Biji Nangka - Cicilia, Siska (Faculty of Agriculture Science & Technology, 2024)
The purpose of this study was to determine the quality of sweet corn ice cream added with jackfruit seed flour. This study used CRD with the addition of jackfruit seed flour (EB) namely EB1 (0%, CMC 0.5%) as a control, EB2= 3%, EB3= 6%, EB4= 9%, EB5= 12% and EB6= 15%. Parameters observed were crude fiber content, melting resistance, overrun, and organoleptic quality (taste, color, and texture) by hedonic. The research data were analyzed using ANOVA at a 5% significance level. The data significantly different were further tested using HSD at the 5% level. Jackfruit seed flour added to the manufacture of jackfruit ice cream had a significantly different effect on crude fiber content, resistance, overrun, texture, but not significantly different on taste and color. The increase in the addition of jackfruit seed flour resulted in an increase in crude fiber content, resistance, and overrun. The EB5 treatment (the addition of 12% jackfruit ) had the best quality with a crude fiber content of 1.54%; resistance 47.25 minutes; and 48.15% overrun, taste and texture accepted by the panelists.